UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG MELALUI MEDIA PEMBELAJARAN PAPAN JURANG (PENJUMLAHAN DAN PENGURANGAN) DI SD NEGERI 066055 MEDAN - Yulanda Andriyani; Ambar Wulan Sari; Shofya Sri Harianty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study is a study based on field data, namely observations, tests and interviews with class II teachers at SDN 066055 Medan which revealed that the majority of their students have not been able to do subtraction or addition in series. There are several things that make this happen, for example the limited use of learning media in the mathematics learning process. Then the learning is still carried out monotonously where the teacher only lectures and explains. This study aims to overcome these problems, namely by using the cliff board learning media, students' subtraction and addition calculation skills are improved. This study applies a type of classroom action, with 17 students as subjects. Based on the pre-cycle test carried out, data was obtained that the ability to calculate addition and subtraction in series with a percentage of completeness of 17.64% of 17 students, meaning that only 3 students completed it. The implementation of learning using the cliff board learning media in cycle 1 resulted in a percentage of completeness of 52.94%. However, from cycle 1 it has not reached the desired target and still needs improvement so that reflection and implementation of cycle II were carried out, after implementing cycle 2 the results of the completion percentage were 82.94% so that it increased by 30% from cycle 1. Based on the results of the study, it was found that the implementation of the ravine board media was proven to improve the ability to count, both subtraction and addition in layers of class II students of SD Negeri 066055 Medan.